The significance of cultural-artistic activity among Slovene emigrants : Western Europe - Lukšič-Hacin, Marina (Two Homelands, 2001)
The activity of Slovene emigrants is variegated and mainly in one way or another connected with the cultural-artistic filed. It can be individual, when we speak of individuals-creators, or organised. For an external observer it shows at various performances, festivals and meetings. We can thus arrange the activities of Slovenes in countries of Western Europe into three groups: 1. Activity, connected with performances of guest groups or individuals from Slovenia among Slovene emigrants; 2. Visits of emigrant groups or individual creators to Slovenia; 3. Activity that is realised through cooperation of emigrants among themselves. The latter is intended for emigrants, sometimes to the environment in which they immigrated to. It places the emigrants as performers of their own activity and at the same time acquaint non-Slovene environments with Slovene culture. When we speak of the significance of the cultural artistic activity among emigrants, we must necessarily point out its important role in preserving ethnic (national) identity in the first generation of emigrants, and particularly with their descendants.